Analisis Campur Kode Pada Tiktok Podcast Kesel Aje Dan Dampaknya Terhadap Eksistensi Berbahasa Anak Milenial: Kajian Sosiolinguistik - Ana Dahniar; Rr. Sulistyawati (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
The presence of applications on social media such as TikTok is one proof of the very fast growth of social media. Content on TikTok, such as the Kesel Aje Podcast, is one of the content that is loved by today's youth because it distributes content by mixing the code between Indonesian and English in communicating. This study aims to describe the form of code-mixing in youth communication in the millennial era and its impact on the existence of the Indonesian language which begins to decline with the assumption that code-mixing is something cool, modern, and educated. The method used in this study is a qualitative descriptive method. The data collection technique used in this study is a technique of observing and noting. The source of the data in this study came from the Kesel Aje Podcast video on TikTok which was taken in November-December 2022. The results of this study are (1) there is data which is a form of code mixing in the form of words, namely 7 data, each in the form of a word in a language Javanese, Sundanese and English. (2) there is data which is a form of code mixing in the form of 5 data phrases. Each of these data is in the form of words in two languages, namely Indonesian and English. (3) The form of code mixing in clauses was not found in this study. The positive impact is that it can help the millennial generation express themselves more freely and spontaneously, as well as strengthen their sense of togetherness and group identity. However, there are also negative impacts from its excessive use, such as reducing the ability to communicate effectively in formal situations and paying less attention to correct language rules.